Tim-3 Is Upregulated in NK Cells during Early Pregnancy and Inhibits NK Cytotoxicity toward Trophoblast in Galectin-9 Dependent Pathway - Sun, Jintang (PLoS One, 2016)
NK cells accumulate at the maternal-fetal interface (MFI) and play essential roles in maintaining immune tolerance during pregnancy. The mechanisms that facilitate NK cells tolerance to fetal tissue are largely unknown. T cell Ig and mucin domain-containing protein 3 (Tim-3) is a newly defined molecule with essential immunological function in many physiological and pathological processes. Recent study showed that Tim-3 was involved in the regulation of immune tolerance at MFI. However, whether Tim-3 regulates NK cells cytotoxicity toward trophoblasts is unclear. Here, we showed Tim-3 was mainly expressed by decidual NK cells (dNK) and Tim-3 level in dNK was higher than peripheral NK cells (pNK). Tim-3(+) dNK expressed more levels of mature markers CD94 and CD69 than Tim-3(-) dNK cells and blocking Tim-3 significantly inhibited dNK IFN-γ and TNF-α secretion. Furthermore, we found TGF-β1 may contribute to such up-regulation of Tim-3 in NK cells. Interestingly, blocking Tim-3 enhanced NK cytotoxicity toward trophoblast cell line HTR-8 but not K562. We found HTR-8 expressed Tim-3 ligand Galectin-9, in contrast K562 did not. Small interfering RNA-mediated silencing of Galectin-9 expression enhanced NK cytotoxicity toward HTR-8. We further showed Tim-3/Galecin-9 inhibited NK cytotoxicity toward trophoblast partially via impairing the degranulation process. In addition, clinical data showed that abnormal Tim-3 level on pNK might be associated with recurrent spontaneous abortion (RSA). Thus, our data demonstrate Tim-3/Galectin-9 pathway maintains local tolerance by suppressing NK cytotoxicity toward trophoblasts which may represent a new immunologic tolerance mechanism at MFI.